Analysis in Economics: Peer to Peer Lending as an Inflation Indicator - Syakirah Putri Septian; Muhammad Akbar Almuttaqin (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study analyzes the relationship between peer-to-peer landing and inflation. Peer-to-peer lending is a means of public lending and inflation is an economic indicator that shows price changes. The method used is vector autoregressive which can explain the two-way relationship of two variables and seasonal aspects in time series data. The results of this study are that the two variables influence each other and there is an influence of the time aspect in the time series data.